2019
DOI: 10.1186/s12864-019-6226-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of five deep-sequenced trio-genomes of the Peninsular Malaysia Orang Asli and North Borneo populations

Abstract: BackgroundRecent advances in genomic technologies have facilitated genome-wide investigation of human genetic variations. However, most efforts have focused on the major populations, yet trio genomes of indigenous populations from Southeast Asia have been under-investigated.ResultsWe analyzed the whole-genome deep sequencing data (~ 30×) of five native trios from Peninsular Malaysia and North Borneo, and characterized the genomic variants, including single nucleotide variants (SNVs), small insertions and delet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…As reported, this issue seemed to be worse for larger CNVs, and more recent tools have not improved this, and the problem does not seem to be observed or addressed. Large CNVs, and SVs in general, are still of interest for the impact they have [17] [19] . We presented that the coverage analysis from the same sequencing experiment that was used to call variants could alleviate the problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, this issue seemed to be worse for larger CNVs, and more recent tools have not improved this, and the problem does not seem to be observed or addressed. Large CNVs, and SVs in general, are still of interest for the impact they have [17] [19] . We presented that the coverage analysis from the same sequencing experiment that was used to call variants could alleviate the problem.…”
Section: Discussionmentioning
confidence: 99%
“…As we demonstrate, this seems to be worse for larger (>50 kb) SVs. While these variants may be less common, they are linked to neurological and rare diseases [17] , are associated to blood serum levels of biological compounds [18] and may be linked to adaptations to different environments of human populations [19] ; therefore, detecting them accurately is of scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…Archaeological and population genetic studies suggest the possibility of these populations inhabiting the Southeast Asia region more than 50,000 years ago [54,55]. Although genome sequencing of these populations has been reported, such research has been rather modest [54,56] compared to many genome sequencing initiatives worldwide.…”
Section: Indigenous Populations As the Model Population For Phenomic ...mentioning
confidence: 99%
“…Indeed, most global largescale genomic research studies lack representation of indigenous populations (to name a few, the HapMap Project; 1,000 Genomes Project; Genome Aggregation Database (gnomAD); Simons Genome Diversity Project). Unfortunately, only a handful of studies reported their respective genomic structures and population histories [56,[63][64][65][66][67][68][69][70]. Studies that correlate their genomic structure and phenotypes have been primarily focusing on identifying signatures of positive selection [71][72][73][74].…”
Section: Phenotypic Studies Of Indigenous Populationsmentioning
confidence: 99%